Post-joining thermal characteristics and repair integrity of carbon fiber-reinforced thermoplastic composites during ultrasonic reconsolidation at 20 kHz - Balaji Ragupathi; Lena Burger; Frank Balle (Composites Part C: Open Access)
Ultrasonic reconsolidation offers significant potential to replace traditional adhesive bonding techniques used in the aerospace industries for bonding repair patches to damaged composite structures without resin additives. Temperature, a characteristic variable, is a key factor influencing the quality of joints in ultrasonic welding of thermoplastic composites. In this study, instead of measuring temperature during the joining process, the focus was on post-joining analysis on temperature at various hold times and holding forces. The findings revealed that an average hold time of 5 s and a holding force of 750 N produced higher-quality joints with minimal damages to fiber bundles and residual matrix. Additionally, it was recommended that repair patches should only undergo a maximum of two reconsolidation cycles. Beyond this point, the fibers and matrix begins to degrade, leading to a 35% reduction in mechanical performance after the fourth cycle.